A Generalization of ⊕-Supplemented Modules (European Journal of Pure and Applied Mathematics, 2012)
Let M and X be R-modules. We define the X--supplemented modules via the class  B(M,X) as a generalization of -supplemented modules. We show that any finite direct sum of X--supplemented modules is X--supplemented. It is given a number of necessary and sufficient conditions for every direct summand of an  X--supplemented module to be X--supplemented.